2003
DOI: 10.1023/a:1024988929454
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Pharmaceuticals such as finasteride and alpha blockers are used to treat symptoms of benign prostatic hyperplasia (BPH) and are known to cause severe adverse reactions. Accordingly, a search for safer, natural products has been undertaken. Two natural agents (nutraceuticals) have come under recent scrutiny; because natural products, in general, often have evidence of long-term safety. The present study compares the in vivo effects on androgen-induced prostatic enlargement in rats of two nutraceuticals--the wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Three “in vitro models” [18–20] and three animal models [12, 21, 22] were used. All the studies demonstrated/confirmed that pollen extracts show two important pharmacological effects: anti-inflammatory and anti-proliferative.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three “in vitro models” [18–20] and three animal models [12, 21, 22] were used. All the studies demonstrated/confirmed that pollen extracts show two important pharmacological effects: anti-inflammatory and anti-proliferative.…”
Section: Resultsmentioning
confidence: 99%
“…Several animal models showed that pollen extract has a possible effect on the prostate via the androgen metabolism [21]. Talpur and co-workers demonstrated that pollen extract decreased the size of the prostate in androgen-induced prostatic enlargement in rats [21].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, these clinical studies confirmed the efficacy of this drug by the relief of CP/CPPS symptoms and suppression of prostate-specific antigen (PSA) (Togo et al, 2018). In addition to clinical reports, the efficacy of Cernitin® in the inhibition of proliferation and inflammation has been validated in preclinical studies (Asakawa et al, 2001;Kamijo, Sato, & Kitamura, 2001;Talpur, Echard, Bagchi, Bagchi, & Preuss, 2003). The antiinflammatory role of Cernitin® is mainly attributed to its inhibitory effect on inflammatory mediators like proinflammatory cytokines tumour necrosis factor-α (TNF-α), interleukin (IL)-6, and IL-1β (Asakawa et al, 2001).…”
mentioning
confidence: 79%
“…Studies that have found saw palmetto administration or treatment reduced androgen action support this belief [11,12,13,14,15]; however, not all studies have found that saw palmetto inhibits 5α-reductase or has anti-androgen action [16,17,18]. The believed bioactive components of saw palmetto are fatty acids and phytosterols.…”
Section: Introductionmentioning
confidence: 99%